Design of a solar steam ejector refrigeration system - Tan, Chin Han. (2009)
The Solar Powered Combined Ejector-Vapour Compression Cycle makes use of a dual purpose pre-cooler unit to connect the Ejector Refrigeration Sub-Cycles (ERSC) and the Vapour-Compression Sub-Cycles (VCSC). In this project, the student explored the functionality of the system that uses water as the refrigerant at the ERSC and R-134a as the refrigerant for the VSCS. Both are economically attractive and environmentally safe as they conform to all the ozone preserving regulations well. The project also covered the relationship between pressure and temperature, coefficient of performance as well as the advantages and disadvantages of using water as a refrigerant.